Student`s research initiatives in the study of strategic planning of regional development - Malchykova, Daria; Korobov, Volodymyr; Pylypenko, Ihor (Human Geography Journal, 2017)
An article describes methodological foundations and principles of the various aspects of the process of strategic planning of regional development study. One of the priorities of innovative pedagogical and methodological work in teaching the competence approach appears. Competence in this approach is the ability of students to solve concrete tasks of regional development evaluation. According to dalto-competence approach the following principles were offered: scientific, systematic, interdisciplinary approach, the close connection with practice, study of the problem of strategic planning of regional development in the context of the theory of centre-periphery relations, taking into account modern theories and indicators of human capital development; hands-on active student participation in research and social work on the elaboration of a regional development strategy. During lectures and workshops the idea of the possibility and the need of comprehensive social and economic indicators for evaluating the effectiveness of regional management have developed. An instructor of courses had a problem – students’ mastery of modern measuring the level of regional development methods. This includes mastering acquaintance with the latest methods and measurement of students’ design skills indexes of regional development and their use for comparative analysis of regional development. In a shortage of own resources lacking to peripheral universities to conduct their own research they could be an educational school for students. It is extremely important to the teachers and students to be involved in the implementation of research projects of local NGOs that can offset this deficiency. Solving scientific and practical problems in process of strategic planning of regional development was provided by a set of research and educational activities: clarification of the concept of "region" using the methodology of a systematic analysis and the determination of the characteristics of regional socio-economic system. Students noted the importance of determination of the characteristics of regional socio-economic system; they used general scientific methods of generalization, systematization, axiomatic method, deduction, induction, comparative historical method and so on. SWOT-analysis was also widely used.